Boundary values of discrete monogenic functions over bounded domains in $$ \mathbb{R}^3 $$ - Cerejeiras, Paula (2019)
In this paper we are going to study boundary values for discrete monogenic functions over bounded spatial domains. After establishing the discrete Stokes formula and the Borel–Pompeiu formula we are going to construct discrete Plemelj–Sokhotzki formulae, discrete Plemelj projections and discrete Hardy spaces. A further extension to the n-dimensional case can be done in a straightforward way based on the results presented in this paper.